2016
DOI: 10.1113/jp272730
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training preserves vagal preganglionic neurones and restores parasympathetic tonus in heart failure

Abstract: Exercise training is an efficient tool to attenuate sympathoexcitation, a hallmark of heart failure (HF). Although sympathetic modulation in HF is widely studied, information regarding parasympathetic control is lacking. We examined the combined effects of sympathetic and vagal tonus to the heart in sedentary (Sed) and exercise trained (ET) HF rats and the contribution of respective premotor and preganglionic neurones. Wistar rats submitted to coronary artery ligation or sham surgery were assigned to training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
(143 reference statements)
0
19
0
2
Order By: Relevance
“…At the 1st, 2nd, 3rd, 4th, and 5th months chronic catheters (Tygon Tubing, Critchley, Australia: 2 cm of 0.28:0.61 connected to 7 cm of 0.50:1.50 ID:OD) were implanted in the left femoral and left carotid arteries under anesthesia (ketamine, 80 mg/kg plus xylazine, 12 mg/kg, ip ). They were treated sc with analgesic (ketoprofen 1%, 2 mg/kg; Biofarm, Jaboticabal, Brazil) and enrofloxacin (Baytril 5 mg/kg, Bayer Sao Paulo, Brazil) and allowed to recover for 24 h. Time-course changes of resting arterial pressure (AP) were recorded for 30–40 min (computer, 2,000 Hz of sampling frequency, LabChart Pro, ADInstruments Bella Vista, NSW, Australia) on the next day in conscious unrestrained rats, as previously described (Masson et al, 2014 ; Ichige et al, 2016 ). At the 1st, 3rd, and 5th month after AP recordings, 10 kDa fluorescein isothiocyanate dextran (FITC, 10 mg/mL, Sigma Aldrich, USA) plus 70 kDa rhodamine B isothiocyanate dextran (RHO, 10 mg/mL Sigma Aldrich, USA), 286 μL/100 g each, were administered at a slow rate (70 and 300 μL/min in rats aged 1 and 3–5 months, respectively) via the carotid artery and allowed to recirculate for 20 min (Biancardi et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…At the 1st, 2nd, 3rd, 4th, and 5th months chronic catheters (Tygon Tubing, Critchley, Australia: 2 cm of 0.28:0.61 connected to 7 cm of 0.50:1.50 ID:OD) were implanted in the left femoral and left carotid arteries under anesthesia (ketamine, 80 mg/kg plus xylazine, 12 mg/kg, ip ). They were treated sc with analgesic (ketoprofen 1%, 2 mg/kg; Biofarm, Jaboticabal, Brazil) and enrofloxacin (Baytril 5 mg/kg, Bayer Sao Paulo, Brazil) and allowed to recover for 24 h. Time-course changes of resting arterial pressure (AP) were recorded for 30–40 min (computer, 2,000 Hz of sampling frequency, LabChart Pro, ADInstruments Bella Vista, NSW, Australia) on the next day in conscious unrestrained rats, as previously described (Masson et al, 2014 ; Ichige et al, 2016 ). At the 1st, 3rd, and 5th month after AP recordings, 10 kDa fluorescein isothiocyanate dextran (FITC, 10 mg/mL, Sigma Aldrich, USA) plus 70 kDa rhodamine B isothiocyanate dextran (RHO, 10 mg/mL Sigma Aldrich, USA), 286 μL/100 g each, were administered at a slow rate (70 and 300 μL/min in rats aged 1 and 3–5 months, respectively) via the carotid artery and allowed to recirculate for 20 min (Biancardi et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach was taken in rats by Ichige et al. where sympathetic tone was calculated as ‘HR after atropine minus intrinsic HR’ and parasympathetic tone as ‘HR after atenolol minus intrinsic HR’ . However, the most important finding regarding pharmacological blockade in the current study was confirmation that the anticipated parasympathomimetic effect of pyridostigmine administration correlated with accelerate heart rate recovery in rats.…”
Section: Discussionmentioning
confidence: 62%
“…While central mechanisms underlying sympathetic hyperactivity in CHF has been extensively studied [21,22], there is scarce information available regarding the effect of CHF on central mechanisms regulating parasympathetic outflows. A study reported that preganglionic parasympathetic neuronal cells were reduced in the nucleus ambiguus and dorsal vagal motor nucleus in rat medulla with CHF when compared with those in healthy controls, explaining the decreased resting parasympathetic tone [23]. Supraspinal cardiovascular regulatory mechanisms may also be involved in parasympathetic hyperresponsiveness to stressors including fear in CHF.…”
Section: Discussionmentioning
confidence: 99%